The Impact of Television and Mobile Device Screens on the Development of Children Aged 0 to 3 Years Students - Żytka-Rydosz, Ewa (Rzeszów University Press, 2025)
In the digital era, infants and toddlers are frequently exposed to screen media. This article evaluates effects of screen exposure on children aged 0–3 years. A narrative integrative review synthesising empirical studies, meta-analyses, international and national guidelines, and recent reports, with focus on exposure measurement and contextual moderators (content quality, caregiver mediation, socioeconomic factors). Excessive, unmediated screen exposure is associated with delayed expressive language, reduced contingent face-to-face interaction, poorer sleep quality and delayed sleep onset (notably with evening use), lower spontaneous physical activity, and challenges in behavioural self-regulation. Conditional benefits – such as video-calls and targeted educational or therapeutic apps – emerge mainly when media are age-appropriate and used with active caregiver engagement. Heterogeneity of measures and predominance of cross-sectional studies limit causal inference. Recommend minimizing non-interactive screen time for under-3s, avoiding screens before bed-time, promoting caregiver-mediated uses and family media plans, and prioritizing longitudinal and intervention research.
Keywords: child development; digital media; television; smartphone; language development; emotional development